Prevalence and antibiotic susceptibility profiles (2016)
Introduction. Food contamination with Listeria monocytogenes is on the increase posing threats to public health with growing trends in food products recalls due to suspected Listeria contamination. Methods. We conducted a cross-sectional study to determine the prevalence and antibiotic susceptibility profiles of Listeria monocytogenes (Lm) among 71 randomly selected poultry farms in Oyo State, Nigeria. A total of 450 samples comprising cloacal swabs (426) and randomly selected dressed chicken meat (24) were cultured for Lm isolation using BrillianceTM Selective Listeria Agar with antibiotics and microbial load count with Nutrient Agar. Further identification was done using microscopic, biochemical characterization and antibiotic sensitivity tests. Data were analysed using bivariate analysis and student t-test. Results. An overall prevalence of 91.8% Lm contamination was obtained comprising 91.5% (390/426) in cloacal swabs and 95.8% (23/24) in meat. The prevalence of Lm in cloacal samples was significantly associated with poultry type (p = 0.008) and breed (p = 0.000. In addition, all the flocks had at least one positive sample yielding 100% flock prevalence. Antibiotic sensitivity test revealed that most of the isolates were resistant to common antibiotics like Ampicillin-cloxacillin and cefuroxime. Conclusions. The results revealed a high level of contamination with Lm in the poultry flock and meat and the observed resistance to most common antibiotics has implications for future disease control as well as public health. There is need to step up routine screening of food animal products for Listeria contamination as well as measures towards reducing such contaminations.